(untitled) (Research, Society and Development, 2021)
This study aimed to identify the impacts experienced by nursing professionals in the face of grief after the death of patients in the emergency unit. This is a descriptive and exploratory research, qualitative in nature, through data collection with 17 nursing professionals who work in the emergency unit of a municipal hospital in the city of Foz do Iguaçu. After transcribing the interviews, the results were analyzed using the Content Analysis technique by Laurence Bardin (2016). Thus, data were grouped into three categories: understanding the death process, feelings about the death of patients and coping with the grieving process. Thus, through this study, it was identified that professionals suffer impacts with the death of patients, thus causing feelings of sadness, crying, and even a feeling of impotence to accept the loss of a loved one. Therefore, it is concluded that it is essential to include the subject of death and grief in continuing education in order to prepare nursing professionals to deal with the grieving process after the loss of patients, especially in the emergency unit, where the occurrence of deaths is higher.